How Economic, Political and Institutional Factors Influence the Choice of Exchange Rate Regimes? New Evidence from Selected Countries of the MENA Region - Najia Maraoui; Thouraya Hadj Amor; Islem Khefacha; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, we investigate how economic, political and institutional factors affect the choice of exchange rate regimes, using data on eight MENA (Middle East and North Africa) countries over the 1984-2016 period. Specifically, we run random-effects ordered probit regressions of the likelihood of exchange rate regimes on potential determinants of exchange rate regimes. Three important findings emerge from the analysis. i) Political and institutional factors play an important role in determining the exchange rate regime in MENA countries: a democratic political regime and a low level of corruption increases the probability to opt for a fixed regime. While, strong governments, political stability such as less internal conflicts and more government stability, more law and order enforcement and left-wing Government decreases the probability to opt for a fixed regime. ii) Bureaucracy, independent central banks, elections, terms of trade as well as the monetary independence have no effect on the choice of exchange rate regimes. iii) Financial development is not a robust determinant of the choice of exchange rate regimes. Our results still hold when considering alternative specifications and have important implications for policy makers in MENA countries.
Keywords: C23; F33; F55; H80; 330; exchange rate regimes; country risk; political and institutional factors; panel data; ordered probit regression; MENA